Risk Screening, Early Detection, and Management of Acute Popliteal Artery Thrombosis Following Total Knee Arthroplasty: Three Case Reports - Vikas Kulshrestha; Pardeep Kumar; Anjan Prabhakara; Munish Sood; Soma Kulshrestha; Manu Mohan (Vascular Specialist International, 2025)
Acute limb ischemia (ALI) is an infrequent but potentially devastating complication that can occur after total knee arthroplasty (TKA). Currently, there is a lack of structured protocols for screening, prevention, early detection, and management of ALI in the context of TKA. With the increasing volume of TKAs performed, some senior surgeons have encountered such complications and formulated protocols and clinical care pathways for managing ALI following TKA. This article presents three cases of acute popliteal artery thrombosis (PAT) after TKA, each with different clinical presentations and management strategies, encountered by a single senior arthroplasty surgeon. Although rare, PAT remains a serious complication of TKA. In today’s high-volume surgical practice, arthroplasty surgeons should ensure careful risk screening and implement preventive strategies. Protocols must be implemented to timely detect and promptly intervene the PAT to prevent adverse outcomes.